PENGARUH ALAT BUKTI HASIL TES URIN MELALUI PEMERIKSAAN LABORATORIUM FORENSIK TERHADAP PUTUSAN YANG DIJATUHKAN HAKIM DALAM TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA (Studi Putusan Pengadilan Negeri Yogyakarta Nomor159/Pid.B/2010/PN.Yk) - Endbram Riaditya dan Tuhu Setiawan, Anggraeni Yuko Isnawangsri (GEMA, 2015)
Legal research entitled The Effect of Evidence Through The Urine Test Results Of Forensic Laboratory Examination Towards Decision Handed Down by Judges in Drugs Abuse Crime (Case Study of The Yogykarta District Courtâs Decision No. 159/Pid.B/2010/PN.Yk), aimed to determine the suitability of forensic laboratory urine test results as evidence by the provisions contained in the KUHAPÂ and its influence on the judge consideration in decisions.This legal research is using normative research method with prescriptive and applied characteristic. So in this legal research using case approach. Sources of legal materials in this research is the primary legal materials and secondary legal materials.Â This legal research is collecting legal material by literature study.Â Legal materials analysis that are deduced by the method of syllogism, the filing of the major and the minor premise and then draw ratio decidendiÂ conclusions.In this research it can be seen that the urine test results through forensic laboratory examinations be referred to as valid documentary evidence because comply with the characteristics of documentary evidence in accordance with the provisions of Article 184 paragraph (1) letter c in conjunction with Article 187 paragraph b and c KUHAP, although not mentioned implicit in Article 184 of the KUHAP. In its decision, the judges used evidence urine test results through forensic laboratory tests on its consideration in decisions, so the judge set the defendant was legally and convincingly met the second charge, namely Article 127 paragraph (1) letter a of Act No. 35 of 2009 on Narcotics (Drugs Abuse). It can be concluded that the results of urine tests through forensic laboratory examinations influence the decision handed down by the judge in the case.The imposition of criminal sanctions in accordance with Article 183 in conjuction Article 193 paragraph (1) KUHAP.